PENGARUH SUKU BUNGA, NILAI TUKAR, PERTUMBUHAN EKONOMI, KINERJA KEUANGAN, KEPUTUSAN PENDANAAN, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - wijaya, dwi nova (Universitas Tanjungpura, 2021)
Value of the firm illustrates how well or not management manages its wealth. The firm's high value can increase prosperity for shareholders, so it can influence investor perception of the company. Every company is required to be able to process the important functions that exist in the company effectively and efficiently so that the company can be superior. Value of the firm can be influenced by macro-economic conditions in a country and micro-economics in industrial sectors. This study aims to test macro-economic factors, namely, the influence of interest rates, exchange rates, economic growth and micro-economics, namely financial performance, funding decisions and investment decisions on the value of the firm. The population of this research is 100 companies at Kompas 100 listed on the Indonesia Stock Exchange in 2015 – 2019. Samples of this study as many as 51 companies were selected based on purposive sampling techniques. The data analysis method used is multiple linear regression analysis. The results showed that there is a negative and insignificant influence of interest rates, economic growth on the value of the firm. Exchange rates and investment decisions have a positive and insignificant effect on the value of the firm. Financial performance has a positive and significant effect on the value of the firm. Financial decisions have a negative and significant effect on the value of the company.